Factors That Influence The Thinking System - Nurusydiyati, Nurusydiyati; Ali, Hapzi (International Journal of Advanced Multidisciplinary, 2023)
The Factors that influence systemic thinking, is a scientific literature review article. The purpose of writing this article is to build hypotheses about the influence between variables that will be used in further research, research objects in online libraries, Google Scholar, Mendeley, and other online media, methods research using the library research method Qualitative descriptive analysis, the results of this article, 1} The environment greatly influences systemic thinking, 2} Limits in the system also affect systemic thinking, 3} The process of thinking influences systemic thinking.